Accuracy in judgment the difficulty score in elite rhythmic gymnastics individual routines - Leandro, C.; Avila-Carvalho, L.; Sierra-Palmeiro, E.; Bobo, M. (Science of Gymnastics Journal, 2015)
The main goal of this study was to analyse the accuracy in judging the Difficulty score in the Rhythmic Gymnastics Kiev World Championship 2013. The accuracy was determined analysing the judges` agreement on the evaluation of the routines difficulty elements. 1152 difficulty forms concerning 288 individual routines were analysed - 4 forms per routine, 1 per judge. To allow the comparison between gymnasts with different levels the individual routines were clustered into 3 subgroups according to their final ranking competition. Body difficulty elements were organized, according to the composition requirements stated in the RG Code of Points (FIG, 2012). Non-parametric tests - Cochran's Q and Chi-Square Tests were applied to determine whether there were significant differences between groups. As main results we can point out that in general the judges did not agree on difficulty evaluation in 40% of the elements. The level of accuracy was lower in the second part of the ranking, and in the Mastery and DER difficulty elements.